Marital captivity: divorce, religion and human rights - Rutten, S. W. E.; Deogratias, Benedicta; Kruiniger, Pauline (Eleven International Publishing, 2019)
This collected edition by experts from all over the world, reflects a multidisciplinary approach to marital captivity and shows a multifaceted view of this widespread phenomenon. Marital captivity is a social and human rights problem that occurs within religions or religious communities worldwide. It is defined as a situation in which one or both spouses, but predominantly the wife, is unable to terminate a religious marriage, consequently trapping that spouse within the marriage against her or his will. As such it is a form of forced marriage and violence against women. Because of its severe social, legal, and economic implications, the phenomenon is approached from different perspectives: anthropological, sociological and legal. In thirteen chapters the book discusses the practice of marital captivity and human rights approaches, solutions and best practices to marital captivity. It is therefore a must-read for civil society, academics, legal practitioners such as solicitors, the judiciary, notaries and registrars, policy makers, and all other practitioners and NGO?s concerned with family issues and violence against women